Differential inhibition of polymorphonuclear leukocyte recruitment in vivo by dextran sulphate and fucoidan - N. Van Osselaer; M. Rampart; A. G. Herman (Mediators of Inflammation)
The selectin-mediated rolling of leukocytes along the endothelial cells is a prerequisite step followed by firm adhesion and extravasation into the inflamed tissue. This initial contact can be suppressed by sulphated polysaccharides. We have studied the effect of sulphated polysaccharides on the ultimate polymorphonuclear leukocyte (PMN) recruitment and plasma leakage in rabbit skin in response to intradermal injection of various inflammatory mediators. PMN infiltration evoked by various PMN chemoattractants (FMLP, C5a desArg, LTB4 and IL-8) was significantly inhibited after intravenous injection of dextran sulphate (25 mg/kg), heparin (2 × 90 mg/kg) or fucoidan (1 mg/kg). PMN-dependent plasma leakage was equally well reduced by the different sulphated polymers. Vascular permeability induced by histamine or thrombin acting via a PMN-independent mechanism was not reduced. Fucoidan was the only polysaccharide able to suppress IL-1-induced PMN infiltration for 60–70%. Local administration of dextran sulphate had no effect on PMN-dependent plasma leakage. Differential inhibition of PMN recruitment was determined after injection of dextran sulphate or fucoidan depending on the type of insult. Therefore, these results suggest that different adhesion pathways are utilized during PMN recruitment in vivo in response to chemoattractants and IL-1.